Extensive polymorphism of Ra86 genes in field populations of Rhipicephalus appendiculatus from Kenya - Kamau, L.M.; Skilton, Robert A.; Githaka, Naftaly W.; Kiara, Henry K.; Kabiru, E.; Shah, Tushaar; Musoke, A.J.; Bishop, Richard P. (Elsevier, 2016)
Commercial vaccines based on recombinant forms of the Bm86 tick gut antigen are used to control the southern cattle tick, Rhipicephalus microplus, a 1-host species, in Australia and Latin America. We describe herein sequence polymorphism in genes encoding Ra86 homologues of Bm86 in the brown ear tick, Rhipicephalus appendiculatus, isolated from four Kenyan field populations and one laboratory colony. Sequencing of 19 Ra86 sequences defined two alleles differentiated by indels, encoding 693 amino acids (aa) and 654 aa respectively, from the Muguga laboratory reference strain. Ra86 sequences were also determined from gut cDNA from four field populations of R. appendiculatuscollected in different livestock production systems in Kenya. Analysis of approximately 20 Ra86 sequences from each of the four field sites in central and Western Kenya; Makuyu, Kiambu, Kakamega and Uasin Gishu, revealed three additional size types differentiated by 39–49 amino acid indels resulting in a total of 5 indel-defined genotypes. The 693 aa type 5 was isolated only from the laboratory tick stock; genotypes 1, 2 and 3 were identified in ticks from the four Kenyan field sites and appeared to be derivatives of the shorter RA86 genotype found in Muguga laboratory stock genotype 4. By contrast no large indels have yet been observed between R. microplus sequences from Australia, South America or Africa. Evidence that selection contributes to the observed sequence variation was provided by analysis of ratio of synonymous and non-synonymous substitutions and application of the selective neutrality and neutral evolution tests to the primary data. Phylogenetic analysis clustered sequences from all Ra86 size types and Bm86, into four major clades based on amino acid substitutions, but there was no evidence that these groupings correlated with geographical separation of R. appendiculatus populations